The Genealogy of Salafi Terrorism - Mahdi Abdollahi ziyaedini (رهیافتهای سیاسی و بین المللی)
Salafi terrorism from its inception until now, it has gone through a process of transformation and created different forms of terrorism. Recognition of this process is essential According to the root cause of the development and evolution of this phenomenon. The study seeks to examine Salafist terrorism through documentary study with Using qualitative approach and Foucault's genealogical approach. It seems that the origins and problems of Salafist terrorism have always been external threats, which appear in the form of critical identification with radicalism. Salafist terrorism has evolved in the idea and construction of power. Salafi ideology has evolved from the stage of the idea of ​​Takfir and jihad to the critical Egyptian Salafi discourse and the Salafist terrorist organization from a logistical institution to a kind of umbrella of globalization with decentralized nuclei. Salafi terrorism can be divided into two types: Arab (Saudi Arabia, Egypt and Iraq) and Indian (India, Pakistan and Afghanistan).